EMPLOYEE ACCEPTANCE AND SATISFACTION USING E-OFFICE BY HYBRID MODEL BASED ON TAM & ISSM - Dita Madonna Simanjuntak; Johan Mohammad Palah; Putri Ambarwati (Jurnal Techno Nusa Mandiri, 2024)
E-Office is an electronic mail application both web-based and mobile with the aim of making it easier for users to send, track, and archive letters. The implementation of E-Office applications within agencies certainly has pros and cons from users so it is necessary to do research to find out how users receive E-Office applications. To analyze user acceptance and satisfaction with E-Office applications, it is necessary to test the factors that influence users in utilizing applications. In this study, testing was carried out by combining two models, namely TAM (Technology Acceptance Model) and ISSM (Information System Success Model). The TAM is a widely used model to evaluate user acceptance of new technologies, while the ISSM was developed to analyze successes or failures in the application of information systems. The research method used is quantitative using questionnaire instruments, then the data is analyzed using the R-Square test. The data collected was 50 and then analyzed using SPSS. The user perception criterion shows a number of 0.740 so that the variables of information quality and system quality have a strong correlation with user perception. While both the criteria for perceived ease of use and user intention show a value above 0.75, which is 0.77 so that the variables of information quality and system quality have a very strong correlation with the perception of ease of use, and the variables of user perception and perception of ease of use have a very strong correlation also to user intentions in using E-Office applications.